2021
DOI: 10.5534/wjmh.210025
|View full text |Cite
|
Sign up to set email alerts
|

A Global Survey of Reproductive Specialists to Determine the Clinical Utility of Oxidative Stress Testing and Antioxidant Use in Male Infertility

Abstract: Purpose The use of antioxidants is common practice in the management of infertile patients. However, there are no established guidelines by professional societies on antioxidant use for male infertility. Materials and Methods Using an online survey, this study aimed to evaluate the practice pattern of reproductive specialists to determine the clinical utility of oxidative stress (OS) testing and antioxidant prescriptions to treat male infertility. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Antioxidants are widely used in the treatment of male infertility. A recent global survey reported that 85.6% of physicians involved in the management of male infertility prescribe antioxidants as a part of their treatment regime ( Agarwal et al, 2021a ). Apart from improving the semen parameters, antioxidant intake increases the sperm DNA integrity without any side effects/complications ( Zini et al, 2009 ; Majzoub et al, 2017 ; Arafa et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants are widely used in the treatment of male infertility. A recent global survey reported that 85.6% of physicians involved in the management of male infertility prescribe antioxidants as a part of their treatment regime ( Agarwal et al, 2021a ). Apart from improving the semen parameters, antioxidant intake increases the sperm DNA integrity without any side effects/complications ( Zini et al, 2009 ; Majzoub et al, 2017 ; Arafa et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidants that counterbalance the increased levels of seminal ROS are widely used in the management of oxidative stress-mediated male infertility ( Agarwal et al, 2021a , b ). Use of antioxidants in treatment of male infertility have shown to improve semen parameters ( Keskes-Ammar et al, 2003 ; Smits et al, 2019 ; Arafa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most systematic reviews and meta-analyses on the topic showed an overall low quality of included studies; therefore, no clear recommendation for antioxidant therapy can be drawn [ 6 , 33 , 34 ]. Nevertheless, in a recent survey, more than 85% of clinicians worldwide stated that they recommend antioxidant therapy in infertile males [ 35 ]. Of note, recent evidence suggests that antioxidant supplements may be harmful and cause unwanted consequences to health [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of antioxidants in male infertility has received significant attention due the central role of oxidative stress in many causes of male infertility [ 25 ]. Antioxidants are also reported to be used extensively by urologists and reproductive medicine specialists globally [ 146 ]. Common antioxidants used in clinical practice include vitamin A (carotenes), vitamin C (ascorbic acid), vitamin E (tocopherols), carnitine, N-acetyl-cysteine (NAC) and Co-Enzyme Q 10 (CoQ 10 ), as well as antioxidant co-factors including selenium, zinc, and folic acid [ 25 147 ].…”
Section: Management Of Oxidative Stress In Varicocelementioning
confidence: 99%
“…As oxidative stress is also closely associated with varicocele pathogenesis, there is significant interest in the use of antioxidants in the management of varicocele as a sole therapy or alongside varicocele repair [ 122 ]. In fact, antioxidants for varicocele in clinical practice is reportedly recommended by 39.9% of reproductive medicine specialists [ 146 ]. Antioxidants may also be a non-invasive alternative to consider prior to surgery or more expensive ART management [ 122 ].…”
Section: Management Of Oxidative Stress In Varicocelementioning
confidence: 99%